Evaluation of anterior fixed appliances on maxillary arch growth in preschool children - Mohamed Ghaly; Nahed Abo Hamila (Scientific Reports)
Abstract This study aimed to evaluate a new modified fixed appliance for rehabilitation of premature loss of anterior teeth in preschool children versus a modified Nance appliance on maxillary arch growth with parental satisfaction. The study was conducted as a clinical trial and it was carried out at Pediatric Dentistry Department, Faculty of Dentistry, Tanta University. Forty preschool children from both genders aged from 3–5 years were included in the study. The selected children were divided into two groups; Group I: Twenty children received a modified fixed bridge. Group II: Twenty received a modified Nance appliance. Evaluation of both appliances on maxillary growth was carried out at baseline, 6 and 12 months. Finally, parental satisfaction was also recorded. It was revealed that, there was continuous maxillary growth in both groups at different follow up periods with no sexual dimorphism, and parental satisfaction was significantly higher in group I than group II. A modified fixed bridge was better than Nance appliance regarding parental satisfaction and it doesn’t interfere with maxillary growth.